Guidelines for Field Trip Activities Designing as A Learning Core and The Moral and Ethical Aspects Development for Music Students in Higher Education - Tissadikun, Natsarun (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The purpose of this article is to present the guidelines for field trip activities designing as a learning core and the moral and ethical aspects development for music students in higher Education. In response to the studies by using field trip education as a core to integrate the knowledge and musical skills that conform to the aptitude of the students majoring in music from practical experience, the implementation, according to the guidelines, has been conducted into 2 activities, namely, music performance and music teaching beyond classroom. The activities have been conducted according to the concept of the 4 Noble Truths which are applied to these activities in order to accomplish in both learning and working achievements for the students and result in learning outcomes in all aspects. We particularly focus on morality and ethics and has applied the principle of proactive learning in conducting music teaching activities beyond the classroom and the learning outcomes on morality, ethics and professional ethics of the students have been fulfilled. This will be a guideline which presents the activities in the form of moral and ethical learner development to be conformed to and appropriate with the aptitude of the students and also the identity of the music major students who will be able to gain both knowledge and showing potential in musical skills together.